# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+3 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+30 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -2\right ) y^{\prime } = x y
\] |
✓ |
✓ |
|
\[
{}\left (x -2\right )^{2} y^{\prime \prime }+\left (x +2\right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 x^{3} y^{\prime }+\left (x^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}2 x \left (x -1\right ) y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 y^{\prime }+4 x y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (-2 x +2\right ) y^{\prime }+\left (x -2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+6 x y^{\prime }+\left (4 x^{2}+6\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x \left (1-x \right ) y^{\prime \prime }-\left (6 x +1\right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (1-x \right ) y^{\prime \prime }+\left (\frac {1}{2}+2 x \right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime \prime }+y^{\prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}4 \left (t^{2}-3 t +2\right ) y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}2 \left (t^{2}-5 t +6\right ) y^{\prime \prime }+\left (2 t -3\right ) y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}3 t \left (t +1\right ) y^{\prime \prime }+t y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {4}{49}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+y^{\prime }+\frac {y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left ({\mathrm e}^{-2 x}-\frac {1}{9}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\frac {\left (x +\frac {3}{4}\right ) y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\frac {\left (x^{2}-1\right ) y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x +1\right )^{2} y^{\prime \prime }+2 \left (2 x +1\right ) y^{\prime }+16 x \left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-6\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+5 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}9 x^{2} y^{\prime \prime }+9 x y^{\prime }+\left (36 x^{4}-16\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+y^{\prime }+36 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+k^{2} x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+k^{2} x^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-5 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -1\right )^{2} y^{\prime \prime }-\left (x -1\right ) y^{\prime }-35 y = 0
\] |
✓ |
✓ |
|
\[
{}16 \left (1+x \right )^{2} y^{\prime \prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-5\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x^{3} y^{\prime }+\left (x^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+3 y^{\prime }+4 x^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y}{4 x} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {26 y}{5} = \frac {97 \sin \left (2 t \right )}{5}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 10 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+5 y = 29 \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+7 y^{\prime }+12 y = 21 \,{\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = 6 t -8
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y}{25} = \frac {t^{2}}{50}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+\frac {9 y}{4} = 9 t^{3}+64
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 50 t -100
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }-4 y = 6 \,{\mathrm e}^{2 t -3}
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }-6 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+8 y = {\mathrm e}^{-3 t}-{\mathrm e}^{-5 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+10 y^{\prime }+24 y = 144 t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \left \{\begin {array}{cc} 8 \sin \left (t \right ) & 0<t <\pi \\ 0 & \pi <t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = \left \{\begin {array}{cc} 4 t & 0<t <1 \\ 8 & 1<t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = \left \{\begin {array}{cc} 3 \sin \left (t \right )-\cos \left (t \right ) & 0<t <2 \pi \\ 3 \sin \left (2 t \right )-\cos \left (2 t \right ) & 2 \pi <t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = \left \{\begin {array}{cc} 1 & 0<t <1 \\ 0 & 1<t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \left \{\begin {array}{cc} t & 0<t <1 \\ 0 & 1<t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = \left \{\begin {array}{cc} 10 \sin \left (t \right ) & 0<t <2 \pi \\ 0 & 2 \pi <t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \left \{\begin {array}{cc} 8 t^{2} & 0<t <5 \\ 0 & 5<t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \delta \left (t -\pi \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 4 \delta \left (t -3 \pi \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \delta \left (t -\pi \right )-\delta \left (t -2 \pi \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+5 y = \delta \left (t -1\right )
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+24 y^{\prime }+37 y = 17 \,{\mathrm e}^{-t}+\delta \left (t -\frac {1}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = 10 \sin \left (t \right )+10 \delta \left (t -1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+5 y = \left (1-\operatorname {Heaviside}\left (t -10\right )\right ) {\mathrm e}^{t}-{\mathrm e}^{10} \delta \left (t -10\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime }+6 y = \delta \left (t -\frac {\pi }{2}\right )+\operatorname {Heaviside}\left (t -\pi \right ) \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime }+6 y = \operatorname {Heaviside}\left (t -1\right )+\delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 25 t -100 \delta \left (t -\pi \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{y \left (x^{3}+1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{1+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = \sqrt {1+y^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{2}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y y^{\prime }+y^{2} = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y^{2} = 2 x y
\] |
✓ |
✓ |
|
\[
{}\left (1+z^{\prime }\right ) {\mathrm e}^{-z} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x^{2}+4 x +2}{2 y-2}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}-\left (1+{\mathrm e}^{x}\right ) y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y}{x -1}+\frac {x y^{\prime }}{1+y} = 0
\] |
✓ |
✓ |
|
\[
{}x +2 x^{3}+\left (y+2 y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {1}{\sqrt {x}}+\frac {y^{\prime }}{\sqrt {y}} = 0
\] |
✓ |
✓ |
|
\[
{}\frac {1}{\sqrt {-x^{2}+1}}+\frac {y^{\prime }}{\sqrt {1-y^{2}}} = 0
\] |
✓ |
✓ |
|
\[
{}2 x \sqrt {1-y^{2}}+y y^{\prime } = 0
\] |
✓ |
✓ |
|